Consumer perceptions matter: A case study of an anomaly in English football - J. James Reade; Jan C. van Ours (Tinbergen Institute, 2024)
In 1983 England's fifth-tier football competition introduced a two-points-for-ahome-win and three-points-for-an-away-win reward system. This system was abolished after three seasons. The anomalous point system may have been introduced to reduce home advantage but the reasons are not fully clear and neither are the reasons for abolishing the system shortly after its introduction. We find that the new point system did not affect match outcomes but it did influence match attendance negatively. We speculate that the alternative point system was perceived as unfair to potential buyers of seasonal tickets or individual match tickets some of whom as a response decided to avoid watching the game in person. Consumer perceptions seem to matter.
Keywords: D12; L83; Z21; 330; Consumer behaviour; sports; football; performance